EFFECT OF GREEN TEA EXTRACT ON INJURED LIVER INDUCED BY ACETAAMINOPHEN IN RABBITS ADULT MALE - Mashi, S. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Green tea is consider as a natural sources of antioxidants used to treat pathological changes occurring as a result of using of many drugs  particularly in the liver tissue. Forty adult male rabbits were randomly divided into four groups (10 rabbits /group) and were treated daily for 30 days as follows: first group (c): is the control group , second group (T1) : rabbits in this group were allowed to ad libitum supply of drinking water containing 2.5 gm /kg b.w of green tea extract , Third group (T2):  rabbits in this group received 500 mg/kg b.w. of acetaminophen orally,  fourth group (T3) : rabbits in this group were allowed to ad libitum supply of drinking water containing 2.5 gm /kg b.w. of green tea extract and received 500mg/kg b.w. of Acetaminophen orally. blood samples were collected for measuring the liver enzymes, cholesterol and triglyceride in blood serum at 15 and 30 days of experience. The results of this study revealed that oral intubation of acetaminophen for 30 days caused hepatic dysfunction manifested by a significant elevation(P